Financial Stability, Leverage, Ineffective Monitoring, Independent Audit Committee, and the Fraudulent Financial Statement - Tjen, Fenny; Sitorus, Tigor; Chasanah, Rina Nur (Universitas Prasetiya Mulya, 2020)
This study aims to develop prior empirical model research of factors influence toward fraudelent financial statement and determine some element of fraud triangle that are financial stability, Leverage, ineffective monitoring and one element of Good Corporate Governance that is independent audit committee influence to fraudulent financial statement. This research topic is important because investors need earnings information as a basic for making investment decision and fraudulent financial statement may affect quality of earnings information received by investors. Data obtained from financial statement of mining company period 2011-2015, data were analyzed with multiple linier regressions with 150 samples collected by purposive sampling technique. Then the authors used Micro soft Excel and SPSS version 24 for processing and analyzing samples. The results showed only financial stability that has a significant influence on fraudulent financial statement, while Leverage, ineffective monitoring and independent audit committee partially has not significant influence toward fraudulent financial statement.